Dietary Fiber and Chronic Disease - Wendy Dahl (EDIS)
Dietary fibers are carbohydrates that are not digestible – it’s what is left over after we digest proteins, fats, starches, and sugars from foods. Plant foods contain dietary fiber and sources include: whole grains, legumes, fruits, vegetables, nuts, and seeds. When we eat foods containing dietary fiber, the fiber moves unchanged through the stomach and small intestine to the colon (large intestine). Once in the colon, fiber works to promote laxation and prevent constipation. However, dietary fiber has many more positive effects on health. This publication describes the relationships between dietary fiber and the prevention and treatment of chronic disease.